Chitty Chitty Bang Bang over the moon - Cottrell Boyce, Frank 1959- (Macmillan Children's Books, 2013)
The Tootings are stuck in 1966! Somebody's stolen Chitty Chitty Bang Bang and left them behind, but that's not their biggest problem. Their biggest problem is that Little Harry's been kidnapped by whoever nicked their magical car. There's only one solution. The Tootings must find the Potts - the family that originally built Chitty. Sharing their combined knowledge of how Chitty works, the families stand a chance of rescuing Little Harry and finding the most brilliant car in the world. But a fiendish criminal has different plans, ones that involve flying Chitty Chitty Bang Bang to the moon and putting an explosive scheme into action